Antifungal Activity of Lactic Acid Bacteria Strains Isolated from Natural Honey against Pathogenic Candida Species - Bulgasem, BY; Lani, MN; Hassan, Z; Yusoff, WMW; Fnaish, SG (Korean Soc Mycology, 2024)
The role of lactic acid bacteria (LAB) in honey as antifungal activity has received little attention and their mechanism of inhibitory of fungi is not fully understood. In this study, LAB were isolated from honey samples from Malaysia, Libya, Saudi Arabia, and Yemen. Twenty-five isolates were confirmed LAB by catalase test and Gram staining, and were screened for antifungal activity. Four LAB showed inhibitory activity against Candida spp. using the dual agar overlay method. And they were identified as Lactobacillus plantarum HS isolated from Al-Seder honey, Lactobacillus curvatus HH isolated from Al-Hanon honey, Pediococcus acidilactici HC isolated from Tualang honey and Pediococcus pentosaceus HM isolated from Al-Maray honey by the 16S rDNA sequence. The growth of Candida glabrata ATCC 2001 was strongly inhibited (> 15.0 mm) and (10 similar to 15 mm) by the isolates of L. curvatus HH and P. pentosaceus HM, respectively. The antifungal activity of the crude supernatant (cell free supernatant, CFS) was evaluated using well diffusion method. The CFS showed high antifungal activity against Candida spp. especially The CFS of L. curvatus HH was significantly (p < 0.05) inhibited growth of C. glabrata ATCC 2001, C. parapsilosis ATCC 2201, and C. tropicalis ATCC 750 with inhibitory zone 22.0, 15.6, and 14.7 mm, respectively. While CFS of P. pentosaceus HM was significantly (p < 0.05) effective against C. krusei, C. glabrata, and C. albicans with inhibition zone 17.2, 16.0, and 13.3 mm, respectively. The results indicated that LAB isolated from honey produced compounds which can be used to inhibit the growth of the pathogenic Candida species.